1993
DOI: 10.1242/dev.119.2.377
|View full text |Cite
|
Sign up to set email alerts
|

The strawberry notch gene functions with Notch in common developmental pathways

Abstract: Genetic and phenotypic analysis of strawberry notch suggests that its gene product is required during embryogenesis and oogenesis, and for the development of the eye, wing and leg. Several lines of evidence suggest that strawberry notch participates together with Notch in many common pathways. A number of strawberry notch mutant phenotypes are similar to those of Notch mutants and can be rescued by an extra copy of wild-type Notch. In addition, mutations in strawberry notch interact strongly with Notch mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Apart from a slight decrease in the body weight, we observed no overt abnormalities in Sbno2 −/− mice, indicating minor roles for SBNO2 during physiological conditions. This differs from other strawberry notch family homologs, including murine SBNO1, which have important or critical roles in development [ 24 , 49 ]. However, our findings support those by Maruyama et al .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a slight decrease in the body weight, we observed no overt abnormalities in Sbno2 −/− mice, indicating minor roles for SBNO2 during physiological conditions. This differs from other strawberry notch family homologs, including murine SBNO1, which have important or critical roles in development [ 24 , 49 ]. However, our findings support those by Maruyama et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the Strawberry notch (sbno) gene of the fly is a component of the Notch signaling pathway, which includes the phenotype of multiple morphological abnormalities, such as notched wings and strawberry‐shaped, disorganized compound eyes (Coyle‐Thompson & Banerjee, 1993; Majumdar et al, 1997; Tsuda et al, 2002). These morphological phenotypes in the wings and eyes of Drosophila mutants are consistent with the abnormalities observed in Notch signaling mutants (Coyle‐Thompson & Banerjee, 1993). Notch and sbno are required for cone cell differentiation in ommatidia development in Drosophila , and sbno and Su(H), a Notch signaling DNA‐binding transcription factor, form a protein complex that activates the expression of Delta (Tsuda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the Strawberry notch (sbno) gene of the fly is a component of the Notch signaling pathway, which includes the phenotype of multiple morphological abnormalities, such as notched wings and strawberry-shaped, disorganized compound eyes (Coyle-Thompson & Banerjee, 1993;Majumdar et al, 1997;Tsuda et al, 2002). These morphological phenotypes in the wings and eyes of Drosophila mutants are consistent with the abnormalities observed in Notch signaling mutants (Coyle-Thompson & Banerjee, 1993). Notch and sbno are required for cone cell differentiation in ommatidia development in Drosophila, and sbno and Su(H), a Notch signaling DNA-binding transcription factor, form a protein complex that activates the expression of Delta (Tsuda et al, 2002).…”
Section: Involvement Of Sbno1 In Notch Signalingmentioning
confidence: 99%
See 2 more Smart Citations